2018
DOI: 10.1080/14763141.2017.1409795
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an unanticipated side-cut on lower extremity kinematics and ground reaction forces during a drop landing

Abstract: Unanticipated direction to cut after landing may alter the lower extremity landing biomechanics when performing landing motions. These alterations may potentially increase the risk of ACL injury. The purpose of this study was to determine if an unanticipated side-cut affects lower extremity landing biomechanics in females. Eighteen recreational female athletes participated in two blocks of testing: the first block of testing consisted of three acceptable trials of anticipated dominant limb and non-dominant lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
4
16
1
Order By: Relevance
“…Therefore, investigating the TTS under unplanned affordances and the inclusion of individuals with a history of severe injuries of the lower limb may be worthwhile. While other authors found alterations of pGRF, 28,47 we observed not such a effect. Therefore, it can be assumed that the study participants were able to equally absorb the landing impact in both conditions, probably by a sufficient degree of anticipatory muscle activity shortly before ground contact and the avoidance of stiff landings (low joint flexion angles of the lower limb).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Therefore, investigating the TTS under unplanned affordances and the inclusion of individuals with a history of severe injuries of the lower limb may be worthwhile. While other authors found alterations of pGRF, 28,47 we observed not such a effect. Therefore, it can be assumed that the study participants were able to equally absorb the landing impact in both conditions, probably by a sufficient degree of anticipatory muscle activity shortly before ground contact and the avoidance of stiff landings (low joint flexion angles of the lower limb).…”
Section: Discussioncontrasting
confidence: 95%
“…Similar findings were made by other trials. 28,47 Although it seems highly plausible that dealing with the unforeseen circumstances occurring in sports requires substantial cognitive resources (e.g. attention, reaction time or inhibitory control), 39 only one study has investigated the association between cognitive function and unplanned landing stability/success.…”
Section: Introductionmentioning
confidence: 99%
“…The same situation is observed in the p values of LR movement, indicating a significant change in cognitive abilities before and after the process. Moreover, these results are supported by the d values shown in pair 3, pair 6, pair 9, pair 12, pair 15, and pair 18 of Table 9 as in [42,56].…”
Section: The Effect Of the System On Physical And Cognitive Developmentsupporting
confidence: 58%
“…Thus, the aim was to examine the weekly physical ability development as stated in [50]. The results obtained from paired t-test are evaluated based on the p value and the effect size (Cohen's d for correlation between two variables) [51] as stated in [42,52]. Independent t-test and effect size were used to examine cognitive ability development by examining changes in joints as weekly pairs from the beginning to the end of the trial period as stated in [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation